Genomewide SNP markers breathe new life into phylogeography and species delimitation for the problematic short‐necked turtles (Chelidae: Emydura) of eastern Australia. Issue 24 (10th December 2018) - Georges, Arthur; Gruber, Bernd; Pauly, Greg B.; White, Duanne; Adams, Mark; Young, Matthew J.; Kilian, Andrzej; Zhang, Xiuwen; Shaffer, H. Bradley; Unmack, Peter J.
Abstract: Understanding the evolutionary history of diversifying lineages and the delineation of evolutionarily significant units and species remains major challenges for evolutionary biology. Low‐cost representational sampling of the genome for single nucleotide polymorphisms shows great potential at the temporal scales that are typically the focus of species delimitation and phylogeography. We apply these markers to a case study of a freshwater turtle, Emydura macquarii, whose systematics has so far defied resolution, to bring to light a dynamic system of substantive allopatric lineages diverging on independent evolutionary trajectories, but held back in the process of speciation by low level and episodic exchange of alleles across drainage divides on various timescales. In the context of low‐level episodic gene flow, speciation is often reticulate, rather than a bifurcating process. We argue that species delimitation needs to take into account the pattern of ancestry and descent of diverging lineages in allopatry together with the recent and contemporary processes of dispersal and gene flow that retard and obscure that divergence. Underpinned by a strong focus on lineage diagnosability, this combined approach provides a means for addressing the challenges of incompletely isolated populations with uncommon, but recurrent gene flow in studies of species delimitation, a situation likely to be frequently encountered. Taxonomic decisions in cases of allopatry often require subjective judgements. Our strategy, which adds an additional level of objectivity before that subjectivity is applied, reduces the risk of taxonomic inflation that can accompany lineage approaches to species delimitation.